Mechanism study on the attenuation of cerebral ischemia–reperfusion injury by LBP extract through regulation of SIRT1/PGC-1α axis - Niu Qingfeng; Peng Jiahui; Zhou Yujia; Li Xiaowen; Liu Ouya; Xin Cheng; Liu Ping; Hei Changchun; Yang Xiao (Translational Neuroscience, 2025)
This study aims to determine if Lycium barbarum polysaccharides (LBP) extract attenuate oxidative stress by regulating the SIRT1/PGC-1α axis, potentially ameliorating oxygen–glucose deprivation/reperfusion (OGD/R)-induced neuronal damage.